Drp1 acetylation mediated by CDK5-AMPK-GCN5L1 axis promotes cerebral ischemic injury via facilitating mitochondrial fission - Jiejie Zhang; Shan Wang; Haitao Zhang; Xiaotong Yang; Xin Ren; Lei Wang; Yihan Yang; Yi Yang; Ya Wen (BMC, 2024)
Abstract The aberrant acetylation of mitochondrial proteins is involved in the pathogenesis of multiple diseases including neurodegenerative diseases and cerebral ischemic injury. Previous studies have shown that depletion of mitochondrial NAD+, which is necessary for mitochondrial deacetylase activity, leads to decreased activity of mitochondrial deacetylase and thus causes hyperacetylation of mitochondrial proteins in ischemic brain tissues, which results in altered mitochondrial dynamics. However, it remains largely unknown about how mitochondrial dynamics-related protein Drp1 is acetylated in ischemic neuronal cells and brain tissues. Here, we showed that Drp1 and GCN5L1 expression was up-regulated in OGD-treated neuronal cells and ischemic brain tissues induced by dMCAO, accompanied by the increased mitochondrial fission, mtROS accumulation, and cell apoptosis. Further, we confirmed that ischemia/hypoxia promoted Drp1 interaction with GCN5L1 in neuronal cells and brain tissues. GCN5L1 knockdown attenuated, while its overexpression enhanced Drp1 acetylation and mitochondrial fission, indicating that GCN5L1 plays a crucial role in ischemia/hypoxia-induced mitochondrial fission by acetylating Drp1. Mechanistically, ischemia/hypoxia induced Drp1 phosphorylation by CDK5 upregulation-mediated activation of AMPK in neuronal cells, which in turn facilitated the interaction of GCN5L1 with Drp1, thus enhancing Drp1 acetylation and mitochondrial fission. Accordingly, inhibition of AMPK alleviated ischemia/hypoxia- induced Drp1 acetylation and mitochondrial fission and protected brain tissues from ischemic damage. These findings provide a novel insight into the functional roles of GCN5L1 in regulating Drp1 acetylation and identify a previously unrecognized CDK5-AMPK-GCN5L1 pathway that mediates the acetylation of Drp1 in ischemic brain tissues.